Evaluasi Standar Proses sebagai Sistem Penjamin Mutu di SMP Negeri 3 Semarang - Vio Amandini Afriliana; Ahmad Mubarok; Rahayu Pristiwati; Mukh Doyin (FKIP, Universitas Palangka Raya, 2025)
In order to improve the quality and quality of a learning process contained in the process standards, there must be an assessment. The aim of this research is to: 1) describe the evaluation of learning planning at SMP Negeri 3 Semarang using procedural text material; 2) describe the evaluation of learning implementation at SMP Negeri 3 Semarang using procedural text material; 3) describe the evaluation results as a quality assurance system. The method used in this research is a qualitative descriptive method, the data source from this research is the teaching module for writing procedural texts written by Mohamad Agus Setiono Class VII Phase D SMP Negeri 3 Semarang and learning videos that have been made using the help of assessment instruments. The steps in data analysis are as follows: 1) read the entire teaching module and watch the video of the learning implementation until completion; 2) analyze using APKG the assessment instrument for planning and implementing learning; 3) assign a score and provide additional evaluation. The results of this research. The evaluation results on learning planning taken from various aspects of assessment can be found to be 77.5%. Next, calculating the results of the learning implementation assessment score was found to be 70%, so it fell into the sufficient scale category. To ensure the quality and quality of learning to write procedural texts, there are several evaluation inputs that can be considered to be implemented in the learning process. The method used should use the Citizen Procedure method.